2014
DOI: 10.7155/jgaa.00318
|View full text |Cite
|
Sign up to set email alerts
|

Superpatterns and Universal Point Sets

Abstract: An old open problem in graph drawing asks for the size of a universal point set, a set of points that can be used as vertices for straight-line drawings of all n-vertex planar graphs. We connect this problem to the theory of permutation patterns, where another open problem concerns the size of superpatterns, permutations that contain all patterns of a given size. We generalize superpatterns to classes of permutations determined by forbidden patterns, and we construct superpatterns of size n 2 /4 + Θ(n) for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 24 publications
1
46
0
Order By: Relevance
“…Angelini et al [1] generalized this result and showed that there exists an n-universal point set of size O (n(log n/ log log n) 2 ) for so-called simply nested planar graphs. A planar graph is simply nested if it can be reduced to an outerplanar graph by successively deleting chordless cycles from the boundary of the outer face.…”
Section: Theorem 1 For Every N ∈ N There Is An N-universal Point Sementioning
confidence: 91%
See 1 more Smart Citation
“…Angelini et al [1] generalized this result and showed that there exists an n-universal point set of size O (n(log n/ log log n) 2 ) for so-called simply nested planar graphs. A planar graph is simply nested if it can be reduced to an outerplanar graph by successively deleting chordless cycles from the boundary of the outer face.…”
Section: Theorem 1 For Every N ∈ N There Is An N-universal Point Sementioning
confidence: 91%
“…A planar graph is simply nested if it can be reduced to an outerplanar graph by successively deleting chordless cycles from the boundary of the outer face. Recently, Bannister et al [2] found n-universal point sets of size O (n log n) for simply nested planar graphs, and O (n polylog n) for planar graphs of bounded pathwidth.…”
Section: Theorem 1 For Every N ∈ N There Is An N-universal Point Sementioning
confidence: 99%
“…Despite more than twenty years of research efforts, the best known lower bound for the value of f (n) is linear in n [6,18], while only an O(n 2 ) upper bound is known, as first established by de Fraysseix et al [7] and Schnyder [20]. Very recently, Bannister et al [2] showed a universal point set with n 2 /4 − Θ(n) points for planar straight-line drawings of n-vertex planar graphs. Universal point sets for planar straight-line drawings of planar graphs require more than n points whenever n 15 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Universal point sets for planar straight-line drawings of planar graphs require more than n points whenever n 15 [5]. Universal point sets with o(n 2 ) points have been proved to exist for planar straight-line drawings of several subclasses of planar graphs, including simply-nested planar graphs [1,2], planar 3-trees [15], and graphs of bounded pathwidth [2].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the n-universal set given by De Fraysseix, Pach, and Pollack [16] has n 2 − O(n) points. This upper bound was improved by Schnyder [28] to n 2 /2 − O(n), then by Brandenburg [8] to 4n 2 /9 + O(n), and finally by Bannister et al [5] to n 2 /4 − Θ(n). On the other hand, Kurowski [23] showed that at least 1.235n points are necessary [23], improving earlier bounds of 1.206n by Chrobak and Karloff [14] and n + √ n by De Fraysseix, Pach, and Pollack [16].…”
Section: Introductionmentioning
confidence: 99%